Pre-existing immune status associated with response to combination of sipuleucel-T and ipilimumab in patients with metastatic castration-resistant prostate cancer. Issue 5 (13th May 2021) - Sinha, Meenal; Zhang, Li; Subudhi, Sumit; Chen, Brandon; Marquez, Jaqueline; Liu, Eric V; Allaire, Kate; Cheung, Alexander; Ng, Sharon; Nguyen, Christopher; Friedlander, Terence W; Aggarwal, Rahul; et al.
Abstract : Background: Sipuleucel-T is a US Food and Drug Administration-approved autologous cellular immunotherapy that improves survival in patients with metastatic castration-resistant prostate cancer (mCRPC). We examined whether administering ipilimumab after sipuleucel-T could modify immune and/or clinical responses to this treatment. Methods: A total of 50 patients with mCRPC were enrolled into a clinical trial (NCT01804465, ClinicalTrials.gov) where they received ipilimumab either immediately or delayed 3 weeks following completion of sipuleucel-T treatment. Blood was collected at various timepoints of the study. Luminex assay for anti-prostatic acid phosphatase (PAP) and anti-PA2024-specific serum immunoglobulin G (IgG) and ELISpot for interferon-γ (IFN-γ) production against PAP and PA2024 were used to assess antigen-specific B and T cell responses, respectively. Clinical response was defined as >30% reduction in serum prostate-specific antigen levels compared with pretreatment levels. The frequency and state of circulating immune cells were determined by mass cytometry by time-of-flight and statistical scaffold analysis. Results: We found the combination to be well tolerated with no unexpected adverse events occurring. The timing of ipilimumab did not significantly alter the rates of antigen-specific B and T cell responses, the primary endpoint of the clinical trial. Clinical responses were observed in 6 of 50 patients, with 3 having responses lasting longer than 3 months. The timing of ipilimumab did not significantly associate with clinical response or toxicity. The combination treatment did induce CD4 and CD8 T cell activation that was most pronounced with the immediate schedule. Lower frequencies of CTLA-4 positive circulating T cells, even prior to treatment, were associated with better clinical outcomes. Interestingly, these differences in CTLA-4 expression were associated with prior localized radiation therapy (RT) to the prostate or prostatic fossa. Prior radiation treatment was also associated with improved radiographic progression-free survival. Conclusion: Combining CTLA-4 blockade with sipuleucel-T resulted in modest clinical activity. The timing of CTLA-4 blockade following sipuleucel-T did not alter antigen-specific responses. Clinical responses were associated with both lower baseline frequencies of CTLA-4 expressing T cells and a history of RT. Prior cancer therapy may therefore result in long-lasting immune changes that influence responsiveness to immunotherapy with sipuleucel-T and anti-CTLA-4.